LOYALITAS PELANGGAN EMINA COSMETICS DITINJAU DARI BRAND TRUST, BRAND IMAGE, DAN KUALITAS PRODUK (STUDI PADA EMINA GIRL GANG AMBASSADOR) - Meliana, Peni Febrianita; Sarsono, Sarsono; Hamidah, Raisa Aribatul (JURNAL ILMIAH EDUNOMIKA, 2024)
This research seeks to assess (1) how Brand Trust effects customer loyalty of Emina Cosmetics products to the Emina Girl Gang Ambassador, (2) how Brand Image influences customer loyalty of Emina Cosmetics products to the Emina Girl Gang Ambassador, (3) how Product Quality influences customer loyalty Emina Cosmetics products to the Emina Girl Gang Ambassador. A quantitative descriptive design was used for this research. The population was taken from Emina Girl Gang Ambassador batch 6, with a Sampel size of 75 respondents. A questionnaire is used in this study, with statistical methods for data analysis such as Coefficient of Determination, multiple linearoregression, t test, and F test. The results indicate that Brand Trust exerts a positive and significant impact on customer Loyalty to Emina Girl Gang Ambassador. Product quality has a positive and significant effect on customer loyalty to Emina Girl Gang Ambassador. Keywords : CustomerQLoyalty, Brand Trust, Brand Image, Product Quality.